Hubungan Religiusitas dengan Agresi Verbal Pemain Game Online - Khaerul Hadad; Efan Yudha Winata (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
Currently, the rise of online games causes many cases of violence, both verbal and non-verbal. However, in everyday life, it is found that online games more often have an impact on verbal violence of players; therefore, this study aimed to determine whether there is a negative relation between religiosity and verbal aggression on online game players in Sumbawa Besar City. The method used in this study was quantitative method. The populations in this study were online game players in Sumbawa Besar City consisting of 70 people who were found based on initial screening. Then, the sampling technique used was saturated sample. The research data was obtained from the research instrument in the form of two scales, namely religiosity scale comprising of 20 items and verbal aggression scale which was adapted from the verbal aggression scale (VAS) consisting of 14 items. The statistical method used was Pearson's Correlation. Based on the results of data analysis, it is known that there is a relation between religiosity and verbal aggression. This can be seen from the research significance value of 0.000 < 0.05 and the correlation coefficient value of -0.436 was included in the category of moderate correlation strength, and showed that there is a negative relation between religiosity and verbal aggression on online game players in Sumbawa Besar City.